Electronic Cross-Border Business Contract Dispute Resolution Model for MSMEs from a Formal Law Perspective - Cicin Nurpasha; Ummi Maskanah (Manunggal Halim Jaya, 2026)
The development of globalization and digital technology has accelerated cross-border electronic commerce, creating broader market opportunities for MSMEs while increasing the risk of legal disputes arising from differences in jurisdictions and legal systems. This study aims to identify the most appropriate, adaptive, and legally feasible dispute resolution model for resolving cross-border electronic business contract disputes involving MSMEs from a formal legal perspective. This research employed a descriptive-analytical method using a normative legal approach supported by empirical data obtained through interviews. The study analyzed primary, secondary, and tertiary legal materials through qualitative legal analysis to examine the legal framework governing cross-border electronic contracts and dispute resolution mechanisms. The findings indicate that conventional litigation and existing alternative dispute resolution mechanisms remain inadequate for MSMEs due to high costs, lengthy procedures, limited access to justice, and jurisdictional challenges. In contrast, Online Dispute Resolution (ODR) offers a more effective model by providing greater efficiency, flexibility, and accessibility in resolving cross-border electronic business contract disputes. The implementation of ODR is legally supported by Law Number 1 of 2024 concerning Electronic Information and Transactions, particularly Article 5, which recognizes electronic documents as valid legal evidence, and Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, particularly Article 4(3), which recognizes electronic communications in dispute resolution. However, Indonesia still requires a comprehensive legal framework governing ODR implementation, institutional authority, and enforcement to strengthen legal certainty and improve legal protection for MSMEs. This study contributes to the development of Indonesian commercial law by proposing a formal legal framework integrating ODR into cross-border electronic business contract dispute resolution and supporting future legal reform and digital commerce governance.